Size matters: first-in-human study of a novel 4 French REBOA device. Issue 1 (8th January 2021) - Power, Adam; Parekh, Asha; Scallan, Oonagh; Smith, Shane; Novick, Teresa; Parry, Neil; Moore, Laura
Abstract : Background: Resuscitative endovascular balloon occlusion of the aorta (REBOA) is an emerging technique used for non-compressible torso hemorrhage. However, its current use continues to be limited and there is a need for a simple, fast, and low profile REBOA device. Our objective was to evaluate the feasibility of a novel 4 French REBOA device called the COBRA-OS (Control of Bleeding, Resuscitation, Arterial Occlusion System). Methods: This study is the first-in-human feasibility trial of the COBRA-OS. Due to the difficulty of trialing the device in the trauma setting, we performed a feasibility study using organ donors (due to the potential usefulness of the COBRA-OS for normothermic regional perfusion) after neurological determination of death (NDD) prior to organ retrieval. Bilateral 4 French introducer sheaths were placed in both femoral arteries and the COBRA-OS was advanced up the right side and deployed in the thoracic aorta (Zone 1). Once aortic occlusion was confirmed via the left-sided arterial line, the device was deflated, moved to the infrarenal aorta (Zone 3), and redeployed. Results: A total of 7 NDD organ donors were entered into the study, 71% men, with a mean age 46.6 years (range 26 to 64). The COBRA-OS was able to occlude the aorta in Zones 1 and 3 in all patients. The mean time of placing a 4 French sheath was 47.7 seconds (n=13, range 28 to 66 seconds). The mean time from skin to Zone 1 aortic occlusion was 70.1 seconds (range 58 to 105 seconds); mean balloon volumes were 15 mL for Zone 1 (range 13 to 20 mL) and 9 mL for Zone 3 (range 6 to 15 mL); there were no complications and visual inspection of the aorta in all patients revealed no injury. Discussion: The COBRA-OS is a novel 4 French REBOA device that has demonstrated fast and safe aortic occlusion in this first-in-human feasibility study. Level of evidence: Level V, therapeutic.